The value of bank capital buffers in maintaining financial system resilience - Bui, Christina; Scheule, Harald; Wu, Eliza (Journal of Financial Stability, 2017)
There is a current controversy concerning the appropriate size of banks’ capital requirements, and the trade-off between the costs and benefits of implementing higher capital requirements. We quantify the size of capital buffers required to reduce system-wide losses using confidential regulatory data for Australian banks from 2002 to 2014 and annual public accounts from 1978 to 2014. We find that a moderate increase in bank capital buffers is sufficient to maintain financial system resilience, even after taking economic downturns into consideration. Furthermore, while banks benefit from paying a lower cost of debt when they have a higher capital buffer, lending volumes are lower indicating that credit supply may be hampered if bank capital levels are too high within a financial system.